School Curriculum And Parents’ Support on Kindergarten Students’ Caring Attitude - Dewi Natalia Puspitasari; Dini Mardila; Kartika Kirana (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2018)
Being care is an important attitude that children learn. Nowadays, it becomes more important when children grow in the environment with working parents, gadgets,television, and individual society. Therefore, Experimental Mangunan Kindergarten hasfour values, and one of the values is ‘being care’. This research was held to find how school curriculum and parents support students’ caring attitude. This is a qualitative research with grounded theory method, which is held in Experimental Mangunan Kindergarten in Yogyakarta. There are two students’ cases in this research. The respondents of the interview were taken purposively. They were the school principal, two teachers, and the students’ parents. Data collections were held by observation, interview, and reading teachers’ journals. The result was that the two students who have not yet caring to others when first entered Mangunan School, were grow to have caring attitude after eight months. These findings show that school curriculum, teachers’ and parents’ relation toward kindergarten students are important part to grow students’ caring attitude.